The Role of Islamic Religious Education Teachers in Shaping Students’ Religious Character: Evidence from an Indonesian Islamic Elementary School - Syamsuriah Syamsuriah; Nur Maallah; M. Nasri Hamang; Andi Fitriani Djollong; Dadang Sumarna (Journal of Education and Learning Sciences, 2026)
This study investigates the role of Islamic Religious Education (IRE) teachers in shaping students’ religious character at Madrasah Ibtidaiyah Negeri (MIN) 1 Enrekang, Indonesia. Religious character development has become a crucial concern in contemporary education due to increasing moral challenges among young learners and the growing influence of digital culture. Employing a descriptive qualitative design, this study collected data through observations, semi-structured interviews, and document analysis involving IRE teachers, school leaders, and students. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while trustworthiness was ensured through triangulation and member checking. The findings reveal that IRE teachers perform multidimensional roles as educators, role models, motivators, and spiritual mentors. Through classroom instruction, religious habituation programs, exemplary behavior, and continuous guidance, teachers facilitate the internalization of Islamic values such as honesty, discipline, responsibility, respect, and social concern. The study further identifies several supporting factors, including a religious school culture, institutional commitment, adequate facilities, and parental involvement. However, challenges remain, particularly differences in family backgrounds and the influence of social media and external environments. The study concludes that religious character formation is a collaborative and continuous process requiring strong synergy among schools, families, and communities. These findings contribute to the growing literature on character education and provide practical implications for strengthening religious character development in Islamic elementary schools.